Learning to think historically through course work: A New Zealand case study. (1st May 2013) - Sheehan, Mark
In New Zealand senior secondary school students are not required to follow a history prescription and up to a half of their courses for national qualifications are based on internally assessed course work where they enjoy a high degree of autonomy over what they choose to study. This paper draws on recent research in five New Zealand schools that examines the extent to which students learn how to think historically when they engage in this type of learning. History is typically only offered as a senior option subject in New Zealand schools and while young people are unlikely to engage with historical thinking prior to this, students who are successful in conducting internally assessed research projects are developing advanced understandings of how the discipline of history operates. It is argued that in this context these students (as novices) are largely developing disciplinary competence and expertise in history by conducting research projects because this process is central to how historians (as experts in the field) critique, interrogate and produce knowledge. While analysis is at an early stage, findings indicate that these students have developed advanced understandings of the interpretive nature of historical thinking, although the question of significance (that in the curriculum is explicitly linked with New Zealand) is proving to be a more difficult concept for students to master.